Chromatin accessibility profiling of Treg cells in acute urticaria - Leilei Wen; Xiaojing Zhang; Qiaoshan Yang; Fusheng Zhou (Epigenetics)
Acute urticaria can be a presenting symptom of anaphylaxis characterized by transient red swellings or fulminant wheals, often accompanied by severe pruritus. Numerous studies have substantiated the important involvement of regulatory T cells (Tregs) in the occurrence of allergic diseases and autoimmune diseases. However, the role of Tregs in the pathogenesis of acute urticaria is unclear. In this study, we found that the frequency of Tregs in peripheral blood mononuclear cells (PBMCs) was decreased in patients with acute urticaria compared with normal controls by flow cytometry. Analysis of Assay for transposase-accessible chromatin with sequencing (ATAC-seq) data identified 28 differentially accessible regions comparing Tregs from healthy individuals and patients with acute urticaria, all showing increased chromatin accessibility in the Tregs from acute urticaria. IL-1b was highly expressed in sera of patients with acute urticaria and the level of IL-1b was moderately positively related to white blood cell count. The elevated expression of IL-1b may be due to the diminished immune-suppressive function following the decline of Tregs in this study. We found that IL1B gene expression was also significantly increased in the skin lesions of both chronic spontaneous urticaria and solar urticaria compared to healthy controls. IL1B might play a key role in the development of acute urticaria and IL1B could be a potential prognostic biomarker and therapeutic target in urticaria.